Similia Similibus. : Joseph Beuys zum 60. Geburtstag. - Bahro, Rudolf; Bastian, Heiner; Beckmann, Lukas; Binder, Jürgen; Bloch, Peter; Brock, Bazon; Christiansen, Henning; Demarco, Richard; Fastabend, Karl; Grass, Jürgen Albert; Harlan, Volker; Kramer, Jürgen; et al. (Köln : DuMont Verlag, 1981)
Beuys, Joseph ; Warhol, Andy ; Genoux, Karin ; Wahner, Nele ; Lueb, Constanze ; Küsters, Franz ; Thiel, Christiane ; Maichel, Berthold St. ; Mahn, Inge ; Rutkowsky, Michael ; Lohaus, Bernd ; Wyss, Dolores ; Müller-Thomsen, Thomas ; Genoux, Wolfgang ; Weber, Achim ; Gutkowski, Mario Kaspar ; Beck, Klaus ; Sacks, Shelley ; Cage, John ; Paik, Nam June ; Hühn, Gerda ; Droese, Felix ; Kunc, Milan ; Groener, Gisela ; Stüttgen, Ursula ; Reuter-Christiansen, Ursula ; Kappler, Ulrike ; Wendker, Wolfgang ; Munker, Johannes ; Berheide, Bodo ; Rosenbach, Ulrike ; Nekes, Werner ; Pinkerton, Josef & Maria ; Vallen, Jürgen ; Rappman, Rainer ; Droese, Irmhild ; Hill, Tony ; Sieverding, Katharina ; Sieber, Günter ; Knoebel, Imi ; Kerger, Horst ; Klophaus, Ute ; Koepplin, Dieter ; Palermo, Blinky ; Immendorff, Jörg ; Dobloug, Jorgen ; Nerdrum, Odd ; Westphal, Rüdiger Axel ; Hafner, Jonas ; Silbermann, Helmut ; Rogalla, Hans ; Stüttgen, Stephan ; Kiefer, Anselm ; Kramer), Jürgen
Duits
boek